Teaching Aids in English Language Teaching: Choosing a Textbook - Horáčková, Michaela (Univerzita Pardubice, 2011)
The work deals with the evaluation of two different textbooks that are used for English language teaching in the ninth grade of Czech basic schools. The theoretical part describes the textbook as a didactic aid in the teaching-learning process. The main themes of the theoretical part are history, function, structure and the processing of the textbooks in sense of communicative competence. At the end ot the theoretical part curricular documents are mentioned, especially The Framework Education Programme for Basic Education (FEP). The practical part evaluates and compares both textbooks on the basis of the communicative competence and FEP.
Didaktické prostředky ve výuce anglického jazyka: Výběr učebnice
Keywords: hodnocení; učebnice; komunikativní kompetence; kurikulární dokumenty; evaluation; textbook; communicative competence; curricular documents